Potential effects of specific gut microbiota on periodontal disease: a two-sample bidirectional Mendelian randomization study - Xu, Meng; Shao, Qiang; Zhou, Yinglu; Yu, Yili; Wang, Shuwei; Wang, An; Cai, Yida (Frontiers in Microbiology, 2024)
Introduction Periodontal disease (PD) presents a substantial global health challenge, encompassing conditions from reversible gingivitis to irreversible periodontitis, often culminating in tooth loss. The gut-oral axis has recently emerged as a focal point, with potential gut microbiota dysbiosis exacerbating PD. Methods In this study, we employed a double-sample bidirectional Mendelian randomized (MR) approach to investigate the causal relationship between specific gut microbiota and periodontal disease (PD) and bleeding gum (BG) development, while exploring the interplay between periodontal health and the gut microenvironment. We performed genome-wide association studies (GWAS) with two cohorts, totalling 346,731 (PD and control) and 461,113 (BG and control) participants, along with data from 14,306 participants’ intestinal flora GWAS, encompassing 148 traits (31 families and 117 genera). Three MR methods were used to assess causality, with the in-verse-variance-weighted (IVW) measure as the primary outcome. Cochrane’s Q test, MR-Egger, and MR-PRESSO global tests were used to detect heterogeneity and pleiotropy. The leave-one-out method was used to test the stability of the MR results. An F-statistic greater than 10 was accepted for instrument exposure association. Results and conclusion Specifically, Eubacterium xylanophilum and Lachnoclostridium were associated with reduced gum bleeding risk, whereas Anaerotruncus, Eisenbergiella, and Phascolarctobacterium were linked to reduced PD risk. Conversely, Fusicatenibacter was associated with an elevated risk of PD. No significant heterogeneity or pleiotropy was detected. In conclusion, our MR analysis pinpointed specific gut flora with causal connections to PD, offering potential avenues for oral health interventions.